Histology of Cryopreserved Neonatal Rat Testes After Intratesticular Allotransplantation - Deng, B.; Kireev, V.O.; Melentyeva, K.V.; Kovalenko, I.F.; Pakhomov, O.V. (My University, 2020)
Cryopreservation and transplantation of testicular fragments and cells are utilized in establishing the germplasm bank of endangered species, line-breeding of animals. Moreover, the transplantation of testicular tissue is involved into investigation of the inborn and acquired defects of testicular tissue. Thus the improvement of cryopreservation and transplantation methods is of great interest. Here, we have compared the findings of histological examination of allotransplanted native and cryopreserved neonatal testis. It has been shown that the usage of DMEM/F12 supplemented with 5 mg/ml bovine serum albumin, 0.05 M sucrose, 20 mM Hepes, 1.5 M dimethylsulfoxide as a cryoprotectant, controlled cooling, preservation at –196°С, water bath warming, followed by intratesticu- lar allotransplantation of neonatal rat testis results in the development of testicular interstitium and spermatogenic epitheliumbof donor organs into recipient’ body
Гистологическое исследование криоконсервированных неонатальных семенников крыс после интратестикулярной аллотрансплантации
Keywords: testis, intratesticular allotransplantation, cryopreservation, immune suppression, immune privilege